Information Technology program students' awareness and perceptions towards personal data protection and privacy - Chen L.F.; Ismail R. (2023)
With the global digitalization of information, the spate of personal data protection cases had disturbed not only Malaysian but netizens over the world. People's awareness and perceptions towards personal data protection had exacerbated the problem of personal data protection. A group of 126 students from the Bachelor of Information Technology program was surveyed on their awareness and perceptions towards the personal data protection. The survey result concluded that the students' perceptions towards personal data protection are conspicuously low but their awareness of the needs to protect their personal data is ostensibly acceptable. The survey results also hint that awareness is not equivalent to understand. Apart from this, the author concludes that the students' sensitivity of personal privacy and personal data protection had paralyzed. Habitually providing personal information through online forms had hypnotized the students' sensitivity of protecting their personal data and privacy. The formulation of Malaysia Personal Data Protection Act 2010 set a general guide line to all data practitioners but the author notice that Malaysia needs a tailor made framework that guide the collection and processing of digital information based on the country's perspectives. Besides, this framework also serves as the tools to educate and mold the netizens' sensitivity towards personal data protection. 2013 IEEE.